Evaluation of incidence and prevention of vulvovaginitis in juvenile stage: Professional article - Koledin Slađana; Mašić Milica; Koledin Bojan; Karadeglija Marija (Association of Nurses Technicians and Midwives, 2016)
Introduction: The nature of juvenile patients' gynecological problems requires a teamwork of experts specialized in different fields of medicine, specifically: juvenile gynecologist, pediatrician and neonatologist, pediatric surgeon and psychologist/pedagogue. Vulvovaginitis is the most frequent gynecological diagnose related to children and it comprises 60% of pediatric gynecological pathology. This condition is the inflammation of vulva and vagina which can be manifested through: itching, pain, burning sensation in vulva area and it is commonly associated with increased secretion. Aim: The analysis of frequency and causis of vulvovaginitis among children and adolescents from 2009 to 2014 and the determination of the most common isolated pathogens. Material and methods: A retrospective study was conducted and the data from medical documentation was used, precisely The Protocol for Juvenile Gynecology, as well as medical reports. The research was conducted in the time period of six years, and the test group was consisted of3792 patients divided into three groups. Results: It was concluded that out of 3792 patients, 1011 were diagnosed with vulvovaginitis, and most common isolated pathogens are Enterococcus, E.coli i Candida albicans. Conclusion: The causes of vulvovaginitis depend on the age of the patient. The most common cause of vulvovaginitis is inadequate hygiene of genital, anal region, and hands. With serving the informations and detailed description of genital hygiene, comes a great success in preventing and reducing the number of vulvovaginitis.